Non-chemical treatments for preventing the postharvest fungal rotting of citrus caused by Penicillium digitatum (green mold) and Penicillium italicum (blue mold) - Papoutsis, Konstantinos (2019)
Background: Citrus is one of the most economically important horticultural crops in the world. Citrus are vulnerable to the postharvest decay caused by Penicillium digitatum and P. italicum, which are both wound pathogens. To date, several non-chemical postharvest treatments have been investigated for the control of both pathogens, trying to provide an alternative solution to the synthetic fungicides (imazalil, thiabendazole, pyrimethanil, and fludioxonil), which are mainly employed and may have harmful effects on human health and environment. Scope and approach: The current study emphasizes the non-chemical postharvest treatments, such as irradiations, biocontrol agents, natural compounds, hot water treatment (HWT), and salts, on the prevention of decay caused by P. digitatum and P. italicum, also known as green and blue molds, respectively. The mode of action of each technique is presented and comprehensively discussed. Key findings and conclusions: In vivo and in vitro experiments in a laboratory scale have shown that the control of green and blue molds can be accomplished by the application of non-chemical treatments. The mechanisms of action of the non-chemical techniques have not been clearly elucidated. Several studies have mentioned that the application of non-chemical treatments results in the synthesis of secondary metabolites with antifungal activities (i.e. polyphenols, phytoalexins) in fruit surface. Moreover, non-chemical treatments may exert direct effects on fungal growth, such as disruption of cell walls, inhibition of metabolic respiration, and disruption of energy production related enzymes.